An enzymatic histamine biosensor based on a screen-printed carbon electrode modified with a chitosan–gold nanoparticles composite cryogel on Prussian blue-coated multi-walled carbon nanotubes. (1st December 2021) - Nontipichet, Natha; Khumngern, Suntisak; Choosang, Jittima; Thavarungkul, Panote; Kanatharana, Proespichaya; Numnuam, Apon
Graphical abstract: Highlights: DAO–CS–AuNPs Cry/PB/MWCNTs/SPCE was first fabricated for histamine detection. The high porosity of CS–AuNPs Cry improves histamine detection sensitivity. A wide linear range and LOD of 1.81 µmol L −1 were obtained for histamine detection. High stability, selectivity and recovery were achieved for histamine detection. The developed biosensor was applied to fish and shrimp sample analyses. Abstract: A histamine biosensor was developed based on a screen-printed carbon electrode modified with Prussian blue (PB) electrodeposited on multi-walled carbon nanotubes covered with a macroporous layer of chitosan–gold nanoparticles composite cryogel (CS–AuNPs Cry). With its high specific surface area and conductivity, CS–AuNPs Cry proved an excellent supporting material for diamine oxidase (DAO) immobilization. PB acted as a redox mediator to promote electron transfer between hydrogen peroxide and the electrode surface. The PB reduction current was measured during the hydrogen peroxide-releasing oxidation of histamine catalyzed by DAO. The proposed biosensor displayed two linear ranges: 2.50–125.0 µmol L −1 and 125.0–400.0 µmol L −1 . The limit of detection was 1.81 µmol L −1 . Reproducibility was good (RSD = 5.46%), operational stability high, long-term stability excellent, and selectivity good. The biosensor determined histamine levels in fish and shrimps with satisfactory recoveries, and the obtained results agreed with those obtained by ELISA.